Alone Beneath The Heaven - Bradshaw, Rita (London Headline, 1998)
Abandoned at birth, Sarah Brown grows up in a 1930's Sunderland orphanage, run by Matron Cox. Upon leaving the home she takes a job as housekeeper where she is more than capable of dealing with her employer's son. When Doctor Rodney comes back into her life, her happiness should be complete.
Keywords: Orphanages -- Great Britain -- Family secrets